The Effect of Occupational Safety and Health Counseling on the Use of Personal Protective Equipment at the Special UPTD of the Medan Hajj Hospital - Nasution, Nurhamidah; Nuraini, Nuraini; Nasution, Ramadhani Syafitri (Universitas Ibn Khaldun Bogor, 2024)
The development of occupational safety and health science in the work environment can be seen with the development of advanced science and technology as well as the emergence of new innovations in the work environment and encouraging companies to improve the knowledge and skills of their human resources. The purpose of this study is to determine the Influence of Occupational Safety and Health Education (K3) on the Behavior of Using Personal Protective Equipment at the Special UPTD of Haji Medan Hospital. This research includes quasi-experimental research. This study uses a one group pretest and pottest design. The population in this study is emergency room nurses at the Special UPTD of Haji Medan Hospital which totals 50 nurses in June-August 2024. The sampling technique in this study is total sampling. The measuring tool in this study uses a univariate and bivariate distribution of non-parametric data with the Wilcoxon test. The results of the Wilcoxon statistical test of both knowledge and attitude obtained a P-value of 0.000. This means that at alpha 5% there is a significant difference in median score between before and after counseling. Meanwhile, in the aspect of action, there was an increase in the number of PPE users between before and after counseling. Because the results of Asymp.Sig of knowledge, attitudes and actions are less than 0.05, H0 is rejected so that there is an influence of occupational health and safety counseling (K3) on the behavior of using PPE. In conclusion, there is an influence of Occupational Safety and Health Counseling (K3) on the behavior of using personal protective equipment at the Special UPTD of Haji Medan Hospital. The suggestions are expected to increase the frequency of counseling and provide information on the importance of using personal protective equipment in the workplace, provide strict sanctions against nurses who do not use personal protective equipment at work, increase the frequency.